SYSTEMATIC REVIEW OF USE OF PATIENT REPORTED OUTCOME IN INTERVENTIONAL RADIOLOGY - Sugih Laksono, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: At present, the implementation of patient-reported outcomes in interventional radiology is not widespread. However, they are capable of significantly impacting the manner in which we deliver healthcare. Patient-reported outcomes provide an avenue for evaluating the perceived advantages that patients encounter subsequent to a medical procedure. Furthermore, they facilitate a comparison of these results with those of open procedures that are more invasive, as perceived by the patient.The aim: This study review of use of patient reported outcome in interventional radiology.Methods: For this systematic review, publications that were published from 2012 to 2023 were taken into account during the search process. This was achieved through the utilization of numerous online reference sources, such as Pubmed and SagePub. The decision was made to exclude review articles, previously published works, and incomplete works.Result: We obtained 94 articles from Pubmed and 110 from SagePub. The therapies we extracted were 1 article from Pubmed and 3 articles from SagePub.Conclusion: Quality of life and patient perception must be respected as one of the parameters of successful therapy. Previous research shows that PRO can be used with good validity and reliability as a therapeutic outcome parameter in many cases, including interventional radiology.